Application of ultrasound towards improving the composition of phenolic compounds and enhancing in vitro bioactivities of Pleurotus pulmonarius (Fr.) Quél extracts. (January 2021) - Amirullah, Nur Amalina; Zainal Abidin, Nurhayati; Abdullah, Noorlidah; Manickam, Sivakumar
Abstract: This study aimed to investigate the effects of conventional (Soxhlet) and ultrasound-assisted (UAE) extractions on the composition, antioxidative, and anti-inflammatory bioactivities of Pleurotus pulmonarius (Fr.) Quél (grey oyster mushroom) extracts. The ultrasound extract E0 (40 min, 300 W) demonstrated the highest antioxidant ability in the Folin-Ciocalteu assay (11.07 mg/g GAE). In comparison, ultrasound extract E3 (30 min, 140 W) showed the highest antioxidant activity in the reducing power assay (0.23 absorbance unit). The E2 extract (50 min, 140 W) had the highest DPPH radical scavenging activity at 15.83%, while the E1 extract (30 min, 460 W) had the best lipid peroxidation inhibition (MDA level of only 7.44 μg/mg LDL). Liquid chromatography-tandem mass spectrometry (LCMS/MS) showed the presence of various phenolic compounds in the Soxhlet and UAE extracts, but hydroxybenzoic acids were found only in the UAE extracts. The UAE extract E2, even at 6.25 μg/mL, showed superior anti-inflammatory activity in its ability to significantly suppress the production of nitric oxide in LPS-stimulated murine macrophage cells, RAW 264.7. UAE extracts E2 and E3 also showed remarkable anti-inflammatory activity, as both suppressed NF-κB. Most of the reported studies so far employed conventional techniques to obtain P. pulmonarius extracts, but ultrasound is a greener alternative option as it shortened extraction time, lowered extraction temperature, and reduced solvent consumption. The application of ultrasound for the extraction of bioactive compounds improved the composition of extracts as well as the bioactivities of P. pulmonarius. Graphical abstract: Image 1 Highlights: Soxhlet and ultrasound extraction techniques were compared to extract bioactive compounds of Pleurotus pulmonarius . Ultrasound extracts demonstrated the highest antioxidant activity. The tests included Folin-Ciocalteu, DPPH-radical scavenging, reducing power, and lipid peroxidation assays. In vitro cell work was done using LPS-stimulated murine macrophage cells, RAW 264.7. Ultrasound extracts showed superior anti-inflammatory activities by decreasing nitric oxide levels and NF-κB activation. Ultrasound enhanced the types of metabolites in the ethanolic extracts of P. pulmonarius .